PENGUATAN KARAKTER PEDULI SOSIAL BERBASIS NILAI-NILAI ISLAM MELALUI AKTIVITAS KEPRAMUKAAN DI MI FATHUL HUDA KALIPAKIS - Muhammad Munir; Arrinda Lutfiani Ayzzahro’; Luvi Octafiani; Mey Anjarwati (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
The decline in students’ social care character has become increasingly evident in contemporary educational contexts. Therefore, educational media that can foster and strengthen social care character are urgently needed. This study aims to examine the integration of Islamic values within scouting activities as an effort to develop students’ social care character at MI Fathul Huda Kalipakis. This research employed a descriptive qualitative approach, with third-grade students serving as the primary data sources. Data were collected through interviews, observations, and documentation, while data credibility was ensured through triangulation techniques. The findings indicate that scouting activities play a significant role in shaping students’ social care character through various programs, including ceremonies, marching drills, knot-tying, hiking, and camping. Furthermore, social care character is reinforced through religious and social habituation, such as praying before and after activities, reciting Surah Al-Fatihah and selected short Qur’anic chapters, engaging in social service activities, helping others, visiting sick peers, and fostering mutual respect. These activities are integrated with Islamic values as reflected in Surah Al-Ma’un (1–3), Ali Imran (102), Maryam (96), Al-Ma’idah (2), An-Nisa (8), and Al-Hujurat (13).